2000
DOI: 10.1097/00000542-200008000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Mechanisms of Ketamine in the Presence and Absence of Peripheral Inflammation

Abstract: These results demonstrated that ketamine produced antinociceptive effects through an activation of the monoaminergic descending inhibitory system, whereas, in a unilateral peripheral inflammation-induced hyperalgesic state, the monoaminergic system did not contribute to the antihyperalgesic effects of ketamine. The mechanisms of the antinociceptive and antihyperalgesic properties of ketamine are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 0 publications
4
40
0
3
Order By: Relevance
“…Tomemori et al (1981) showed that the analgesic effects of ketamine in the tail-flick test disappear following C1 cervical transection in rats, and ketamine analgesia is absent following lesions of the spinal dorsolateral funiculus (Crisp et al, 1991), which contains the descending noradrenergic axons. Kawamata et al (2000) demonstrated that intrathecal yohimbine (an α 2 -adrenoreceptor antagonist) attenuates the analgesic effects of ketamine in the paw withdrawal test. A recent study showed that systemic administration of clonidine (an α 2 -adrenoreceptor agonist) produced analgesia but did not induce Fos in the A6 and A7 groups, and thus presumably caused direct α 2 -mediated antinociception at the dorsal horn (Fukuda et al, 2006).…”
Section: Analgesic Mechanism Of General Anestheticsmentioning
confidence: 99%
“…Tomemori et al (1981) showed that the analgesic effects of ketamine in the tail-flick test disappear following C1 cervical transection in rats, and ketamine analgesia is absent following lesions of the spinal dorsolateral funiculus (Crisp et al, 1991), which contains the descending noradrenergic axons. Kawamata et al (2000) demonstrated that intrathecal yohimbine (an α 2 -adrenoreceptor antagonist) attenuates the analgesic effects of ketamine in the paw withdrawal test. A recent study showed that systemic administration of clonidine (an α 2 -adrenoreceptor agonist) produced analgesia but did not induce Fos in the A6 and A7 groups, and thus presumably caused direct α 2 -mediated antinociception at the dorsal horn (Fukuda et al, 2006).…”
Section: Analgesic Mechanism Of General Anestheticsmentioning
confidence: 99%
“…21 Several behavioural and electrophysiologic studies suggest that ketamine produces antinociceptive effects through activation of monoaminergic descending inhibitory pathways. 19,20,[22][23][24] The mechanism of the antinociceptive effects of ketamine is suggested to depend upon the presence peripheral inflammation. 22 The third purpose of the current study is to clarify the mechanism of the antinociceptive effects of systemic ketamine.…”
Section: Objectifmentioning
confidence: 99%
“…19,20,[22][23][24] The mechanism of the antinociceptive effects of ketamine is suggested to depend upon the presence peripheral inflammation. 22 The third purpose of the current study is to clarify the mechanism of the antinociceptive effects of systemic ketamine. Site of action and involvement of noradrenergic and serotonergic systems were examined in the postoperative pain model.…”
Section: Objectifmentioning
confidence: 99%
“…Ketamine also activates the monoaminergic descending inhibitory pathway at supraspinal sites resulting in antinociception [18]. Although in this research work, there was no clear distinction in the opioid requirements between the two groups, but the ketamine group showed an apparent lower dose of opioid needs in 24 hours.…”
Section: Discussionmentioning
confidence: 61%